2006
DOI: 10.4315/0362-028x-69.2.441
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of Enterohemorrhagic Escherichia coli, Escherichia coli O157, Salmonella, and Listeria monocytogenes in Retail Fresh Ground Beef, Sprouts, and Mushrooms

Abstract: The objective of this study was to determine the prevalence of enterohemorrhagic Escherichia coli (EHEC), E. coli O157, Salmonella, and Listeria monocytogenes in retail food samples from Seattle, Wash. A total of 2,050 samples of ground beef (1,750 samples), mushrooms (100 samples), and sprouts (200 samples) were collected over a 12-month period and analyzed for the presence of these pathogens. PCR assays, followed by culture confirmation were used to determine the presence or absence of each organism. Of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
48
4
1

Year Published

2008
2008
2016
2016

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 103 publications
(55 citation statements)
references
References 10 publications
2
48
4
1
Order By: Relevance
“…Contamination of beef by STEC has been examined by other researchers around the world. In the United States, a recent study by Samadpour et al reported STEC in 3.5% of 1,750 retail ground beef samples collected from stores in Seattle, WA (45). In other countries, STEC was detected in 4% of beef samples in France (43) and 3% of raw beef samples in Australia (11).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Contamination of beef by STEC has been examined by other researchers around the world. In the United States, a recent study by Samadpour et al reported STEC in 3.5% of 1,750 retail ground beef samples collected from stores in Seattle, WA (45). In other countries, STEC was detected in 4% of beef samples in France (43) and 3% of raw beef samples in Australia (11).…”
Section: Discussionmentioning
confidence: 99%
“…Such variations could lead to a big difference in results, since isolation of STEC from stx-positive samples was found to be relatively difficult due to the small number of bacterial cells or the occurrence of free stx-carrying phages in meat samples (43,45). In terms of isolation method, instead of picking multiple colonies randomly from one plate and testing each of them (17,26), colony hybridization with a stx probe would more conveniently detect any STEC in all colonies on each plate and yield more accurate results (18,45). The level of STEC contamination (Ͻ1%) in the NARMS ground beef appeared low compared to reports from other investigators, but caution should be exercised in interpreting this low prevalence.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A baixa ocorrência de L. monocytogenes também foi reportada no trabalho de Yücel et al (2005), que relataram uma frequência reduzida dessa espécie em carnes bovinas, moídas e inteiras, e carne de frango, sendo que somente 6,16% das amostras estavam contaminadas. Samadpour et al (2006) e Mantilla et al (2007 também observaram uma quantidade pequena de carnes moídas contaminadas com L. monocytogenes, 3,5 e 6,7% respectivamente. Apesar das baixas ocorrências, verifica-se que esses alimentos ainda representam risco para saúde dos consumidores.…”
Section: Discussionunclassified